Upregulated SET Promotes Cell Survival Through Activating Akt/NF-κB Signal in Colorectal Carcinoma - Zhu J (Cancer Management and Research, 2020)
Jianjun Zhu,1 Lihong Shi,2 Genlai Du,1 Li Li,1 Ming Liu1 1Department of Medical Cellular Biology and Genetics, Shanxi Medical University, Taiyuan 030001, People’s Republic of China; 2Department of Human Anatomy, School of Basic Medicine, Shanxi Medical University, Taiyuan 030001, People’s Republic of ChinaCorrespondence: Lihong ShiDepartment of Human Anatomy, School of Basic Medicine, Shanxi Medical University, 56 Xinjian South Road, Taiyuan 030001, People’s Republic of ChinaTel/ Fax +86-351-3985176Email czxy12@163.comPurpose: SET has been proven to be an oncogene, which promotes the initiation and progression in several kinds of malignant carcinomas. However, the expression and its functional roles in colorectal carcinoma (CRC) remained unknown.Materials and Methods: CRC tissues samples, CRC cell lines and xenograft mouse tumors were used in this study. The mRNA and protein expressions were detected by quantitative real-time polymerase chain reaction (qRT-PCR), immunohistochemistry (IHC), and Western blot (WB), respectively. siRNAs were used to silence the gene expression. Cell viability, cell proliferation, colony formation, and apoptosis were measured by MTS assay, EdU incorporation assay, plated colony formation assay, and flow cytometry, respectively. Western blot was applied to evaluate the levels of Akt, p-Akt, c-Myc and cyclin D1. Xenograft mouse model was performed to observe the role of SET in vivo.Results: Our results revealed that SET was up-regulated in CRC, and the expression of SET was increased with the development of CRC. SET knockdown in vitro attenuated cell proliferation activity, and increased cell apoptosis in CRC cells. Moreover, the knockdown of SET reduces tumorigenic potential in nude mice. For the mechanism, knockdown of SET promoted the dephosphorylation of Akt, followed by suppressing the translocation of NF-κB to nucleus. In addition, SET knockdown-mediated dephosphorylation of Akt downregulated the expression of c-Myc and Cyclin D1, which inhibited the cell survival in CRC.Conclusion: Our results indicated that SET promoted cell survival via activating Akt/NF-κB signaling pathway in CRC, which strongly suggested that SET might be a potential therapeutic target in the colorectal carcinoma treatment.Keywords: SET, colorectal adenocarcinoma, PP2A, Akt, NF-κB